Assessment of the effectiveness of PMTCT program in eight service delivery points in North Central Nigeria - Oleribe OO (Dove Medical Press, 2018)
Obinna Ositadimma Oleribe,1 Ede Enenche,1 Deborah Udofia,1 Ekei Ekom,1 Princess Ifunanya Osita-Oleribe,1 Jin Un Kim,2 Simon David Taylor-Robinson2 1Excellence and Friends Management Care Centre (EFMC), Abuja, Nigeria; 2Hepatology Unit, Imperial College London, London, UK Background: Mother-to-child transmission (MTCT) of HIV is one of the commonest avenues through which infants are infected with HIV. To achieve an HIV-free generation, MTCT of HIV should be eliminated. Nigeria began prevention of mother-to-child transmission (PMTCT) services 13 years ago, but it still contributes to over one-third of global MTCT burden. We set out to explore and define the effectiveness of PMTCT in selected sites in North Central Nigeria.Methods: We conducted a retrospective secondary data analysis at eight service delivery points in two states. One thousand four hundred and fifty-four mother–infant pair data sets from 2012 to 2016 were extracted and analyzed. Maternal/infant antiretroviral (ARV) services, early infant diagnosis (EID), and final outcomes were reviewed to examine the predictors of MTCT of HIV in these centers.Results: We retrieved 1,454 mother–infant pair data sets. While 89.5% (1,302) of positive pregnant women (PPW) and 92.2% (1,340) of HIV-exposed infants (HEIs) received ARV prophylaxis/ARV treatment (ART), 88.4% (1,285) infants were breastfed with 32.5% still receiving breast milk at the time of dry blood spot (DBS) collection. EID PCR positivity rate was 3.5% (range, 0.0%–11.1%). Facility of delivery (X2=24.99, P<0.00), mother on ARV (X2=48.8, P<0.00), mother having received ARV prophylaxis (X2=89.59, P<0.00), infant having received ARV prophylaxis (X2=58.56, P<0.00), and baby having received cotrimoxazole (X2=55.24, P<0.00) all significantly prevented positive EID results. However, mode of delivery and breastfeeding were not significantly associated with positive EID results.Conclusion: This study supports PMTCT services as it minimizes the transfer of HIV from infected mothers to HEIs. To eliminate HIV and achieve zero new HIV infections, every HIV-positive pregnant woman should receive ARV prophylaxis and should be supported postdelivery to prevent transfer of infection to the newborn. Also, HEIs should receive timely ARV and cotrimoxazole prophylaxis. Keywords: antiretroviral therapy, infectious diseases, prevention of mother-to-child transmission, women, Africa